Analisis Perubahan Tutupan Hutan Pada Kawasan Hutan Lindung KPH Rinjani Timur Pulau Lombok - Dinda Larasati; Muhamad Husni Idris; Markum (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
This study aims to identify changes in forest cover from 2000 to 2022 in the protected forest area of Resort Suela KPH Rinjani Timur. The research was conducted in the protected forest area of Resort Suela KPH Rinjani Timur during April-May 2023. The data sources used in this study include maps and shapefiles of the protected forest area of Resort Suela from KPH Rinjani Timur, as well as satellite images captured on Path 116 and Row 66 for Landsat 7 on August 19th, 2000, and Landsat 8 OLI-TIRS on November 3rd, 2013, and August 16th, 2022, which were obtained from https://earthexplorer.usgs/gov. The research methodology employed is a quantitative descriptive approach. The forest cover classification analysis was conducted using the Supervised Classification and Maximum Likelihood methods. The forest cover in the protected forest area of Resort Suela was divided into six categories: dense forest, medium forest, savanna/grassland, mixed dryland agriculture, shrubland, and open land. Technical terms were explained upon first use, and the text adhered to conventional academic structure, clear and objective language, and precise word choice without bias or subjective evaluations. The result demonstrated a logical flow of information with causal connections between statements. Citations and footnotes were consistently applied, and grammatical correctness was maintained. Forest cover change was analysed through the comparison of forest cover overlay results. In the protected forest area of Suela Resort, there was a decrease in dense forest cover of 477.4 hectares and an increase in moderate forest cover by 345.6 hectares from 2000 to 2013, as well as an increase in mixed dryland agricultural shrub cover. Between 2013 and 2022, there was a decrease in shrub cover of 272.5 hectares and an increase in dense forest cover of 188.5 hectares, as well as a moderate forest cover increase of 55.6 hectares. Overall, compared to the year 2000, there was a decrease in dense forest cover of 289 hectares and an increase in moderate forest cover of 401.7 hectares, as well as mixed dryland agricultural cover.